WAVE2 2019 Pre-Text Elements and Committees - Gomes, Alex Sandro; Moreira, Fernando Joaquim Lopes; Oliveira, Francisco Kelsen de (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2019: Anais do II Workshop on Advanced Virtual Environments and Education, 2019)
Pre-textual elements and committees of WAVE 2 2019.